Efficacy of carvacrol oil against common broilers chickens enteric pathogens. - Radwan, Ismail; Orabi, Ahmed; El-Hanbally, Saber; A. Mabrouk, Hanaa (International Journal of Pharmacology and Toxicology, 2018)
Gastrointestinal tract acts as a selective barrier for the broilers, however a wide range of factors associated with diet and infectious disease agents can negatively affect the delicate balance among the components of the chicken gut and, as a result, affect health status and production performance of birds in commercial poultry industries. Our investigation aimed to determine the incidence of the most common broilers chicken enteric pathogens as Salmonella, E.coli and C.perfringens and also measure efficacy of carvacrol oil on these pathogens. 250 internal organs were analyzed for enteric pathogens in (table 1, 2) which revealed high incidence of E.coli (n=18) followed with Salmonella (n=10) and C.perfringens (n=8).Serotyping of Salmonella isolates showed that the predominant serovars is S.Kentuky (n=3) then S.Typhimurium and S.Infants (n=2), while O114:K90 O78:K80 O25:K11 were the predominant E.coli serotypes (n=4) for each one. Antibiogram revealed that isolates were resistance to Cefotaxime, Amoxicillin, Doxycycline and Enrofloxacin. Results indicated that, MIC of most isolates lowered after 24hr exposure to 0.001% of carvacrol and the growth of tested isolates was inhibited at 0.1% carvacrol concentration.Â Â